2018
DOI: 10.1021/acs.organomet.8b00004
|View full text |Cite
|
Sign up to set email alerts
|

Water-Soluble Mono- and Binuclear Ru(η6-p-cymene) Complexes Containing Indole Thiosemicarbazones: Synthesis, DFT Modeling, Biomolecular Interactions, and In Vitro Anticancer Activity through Apoptosis

Abstract: Indole thiosemicarbazone ligands were prepared from indole-3-carboxaldehyde and N-(un)substituted thiosemicarbazide. The Ru(η 6 -p-cymene) complexes [Ru(η 6 -pcymene)(HL1)Cl]Cl (1) and [Ru(η 6 -p-cymene)(L2)] 2 Cl 2 (2*) were exclusively synthesized from thiosemicarbazone (TSC) ligands HL1 and HL2, and [RuCl 2 (p-cymene)] 2 . The compounds were characterized by analytical and various spectroscopic (electronic, FT-IR, 1D/2D NMR, and mass) tools. The exact structures of the compounds (HL1, HL2, 1, and 2*) were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
56
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 86 publications
(60 citation statements)
references
References 103 publications
4
56
0
Order By: Relevance
“…34,52 The activity of complexes 2 and 3 was also comparable with reported ruthenium-arene complexes against HeLa S3 and A549 cell lines. 53 It is evident from the comparison that our complexes showed good cytotoxic property with the earlier reported ruthenium-arene complexes (Figure 5). Cytotoxicity results indicate higher activity of complexes because of the nature of the chelating TSC/TAA ligand and arene moiety.…”
Section: Resultssupporting
confidence: 73%
“…34,52 The activity of complexes 2 and 3 was also comparable with reported ruthenium-arene complexes against HeLa S3 and A549 cell lines. 53 It is evident from the comparison that our complexes showed good cytotoxic property with the earlier reported ruthenium-arene complexes (Figure 5). Cytotoxicity results indicate higher activity of complexes because of the nature of the chelating TSC/TAA ligand and arene moiety.…”
Section: Resultssupporting
confidence: 73%
“…They demonstrate a wide range of oxidation states, lipophilic character, redox properties, structural diversity, kinetic stability, an ability to bind to biomolecules and the opportunity to tune ligands to control the kinetic properties. In this regard, ligand selection needs to be carefully planned for the development of organometallic drugs [11–14] . Aroylthioureas are known to exhibit antibacterial, antifungal, and anticancer properties.…”
Section: Introductionmentioning
confidence: 99%
“…Eventually, we have found that the thiourea ligand and its Ru‐ p ‐cymene complex displayed a rather unusual coordination mode where they form a strained four‐membered ring. This type of coordination mode was also known for some thiosemicarbazones . The new coordination mode of aroyl/acyllthiourea ligands along with the five different coordination modes was shown in Figure .…”
Section: Introductionmentioning
confidence: 99%